Combining Nitrogen‐Doped Graphene Sheets and MoS2: A Unique Film–Foam–Film Structure for Enhanced Lithium Storage. (4th September 2016) - Shan, Ting‐Tian; Xin, Sen; You, Ya; Cong, Huai‐Ping; Yu, Shu‐Hong; Manthiram, Arumugam
Abstract: With a notable advantage in terms of capacity, molybdenum disulfide has been considered a promising anode material for building high‐energy‐density lithium‐ion batteries. However, its intrinsically low electronic conductivity and unstable electrochemistry lead to poor cycling stability and inferior rate performance. We herein describe the scalable assembly of free‐standing MoS2 –graphene composite films consisting of nitrogen‐doped graphene and ultrathin honeycomb‐like MoS2 nanosheets. The composite has a unique film–foam–film hierarchical top‐down architecture from the macroscopic to the microscopic and the nanoscopic scale, which helps rendering the composite material highly compact and leads to rapid ionic/electronic access to the active material, while also accommodating the volume variation of the sulfide upon intercalation/deintercalation of Li. The unique structural merits of the composite lead to enhanced lithium storage.